Polygamous marriage in the contemporary seventh–day adventist church: The responses of some members - Omotosho, Olabode John (Ilorin journal of religious studies, 2020)
Christians’ responses to religio-cultural life such as polygamy in Africa have generated diverse reactions from some African Christians. In this wise, some argued that the design established by God at creation was that, the marital relationship would be between a man and a woman like Adam and Eve (Gen 2: 22-24). Therefore, monogamy is the biblical foundation for marriage relationship, while some others submitted that considering some African cultural heritages and values of polygamy, the Church in Africa should be tolerant and magnanimous enough to accommodate polygamous members and potential Christian polygamists. And so, the idea of requiring polygamists to drive away all but a wife before baptism is considered inappropriate. The paper adopted the religio-cultural principle, and hermeneutical method to examine African polygamy, the teaching and practice of the Seventh-day Adventist (SDA) Church, and responses of some members on marriage so as to get the desired information. The study found that while the teaching and practice of Christian Church is generally in favour of monogamy, there is no explicit condemnation of polygamy. Therefore, the paper contends that the Church in Africa ought to be tolerant towards African Christian polygamists, teaching them tenets of Christian disposition on marriage without enforcement and condemnation.